2018
DOI: 10.1101/330456
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Isolation and antibiotic profile ofVibriospp. in final effluents of two wastewater treatment plants in the Eastern Cape of South Africa

Abstract: Background: Poorly or partially treated wastewater disposed of can contaminate water and even properly treated sewage can have its problems. The highlight of this danger is wastewater treatment plants serving as reservoir for proliferation of antibiotic resistant organisms. We have reported the state of two wastewater treatment in the Eastern Cape of South Africa which discharge poorly and partially treated effluents. Our aims to identify Vibrio spp. and their antibiotic profiles in treated final effluent disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 65 publications
(92 reference statements)
1
6
0
Order By: Relevance
“…Twenty-nine percent of the Vibrio isolates exhibited resistance against tetracycline, while 71 % of the isolates were susceptible against tetracycline. This report corroborates with the reports of Quilici et al [33]; Raissy et al [35]; Osuolale and Okoh, [32].…”
Section: Discussionsupporting
confidence: 93%
“…Twenty-nine percent of the Vibrio isolates exhibited resistance against tetracycline, while 71 % of the isolates were susceptible against tetracycline. This report corroborates with the reports of Quilici et al [33]; Raissy et al [35]; Osuolale and Okoh, [32].…”
Section: Discussionsupporting
confidence: 93%
“…associated with poorly treated effluent water have caused Vibrio epidemics in various countries (e.g. Haiti, Kenya and South Sudan) (Osuolale & Okoh, 2018). Vibrio spp.…”
Section: Wastewatermentioning
confidence: 99%
“…isolates were positive for the catIV gene. A study done by Osuolale and Okoh (2018) reported that 21.5% of Vibrio spp. ( V. parahaemolyticus , V. vulnificus and V. fluvialis ) isolated from effluent water discharged by wastewater treatment plant (WWTP) showed varied antimicrobial resistance towards ampicillin, chloramphenicol, ciprofloxacin, tetracycline, cefotaxime and trimethoprim‐sulphamethoxazole.…”
Section: Wastewatermentioning
confidence: 99%
See 1 more Smart Citation
“…Vibrio species are known autochthonous populations found in freshwaters and marine sediments worldwide [9,10]. Several species of Vibrio are known to cause a number of diseases in human, including cholera, gastroenteritis and primary septicaemia, and their infections arise from the ingestion of contaminated foods, water, undercooked seafoods and through wounded skin getting direct contact with contaminated water [11][12][13][14]. The upsurge of potentially pathogenic Vibrio species in freshwater resources is partially attributable to global warming induced by hydro-climatic changes [15].…”
Section: Introductionmentioning
confidence: 99%